THE ROLE OF COMMICATIVE LANGUAGE TEACHING EFL. (Ta'limning zamonaviy transformatsiyasi, 2024)
Abstract: EFL (English as a Foreign Language) communicative teaching is an important part of modern educational methods. This approach aims to activate students in the language learning process and develop their communication skills. Communicative teaching focuses on practical application of language rather than theoretical learning. This approach allows students to use English in real-life situations, which increases their confidence.